Muscle-like scaffolds for biomechanical stimulation in a custom-built bioreactor - Rojas-Rojas, Laura; Espinoza-Álvarez, María Laura; Castro-Piedra, Silvia; Ulloa-Fernández, Andrea; Vargas-Segura, Walter; Guillén-Girón, Teodolito (Polymers 2022, 2022)
Tissue engineering aims to develop in-vitro substitutes of native tissues. One approach of tissue engineering relies on using bioreactors combined with biomimetic scaffolds to produce study models or in-vitro substitutes. Bioreactors provide control over environmental parameters, place and hold a scaffold under desired characteristics, and apply mechanical stimulation to scaffolds. Polymers are often used for fabricating tissue-engineering scaffolds. In this study, polycaprolactone (PCL) collagen-coated microfilament scaffolds were cell-seeded with C2C12 myoblasts; then, these were grown inside a custom-built bioreactor. Cell attachment and proliferation on the scaffolds were investigated. A loading pattern was used for mechanical stimulation of the cell-seeded scaffolds. Results showed that the microfilaments provided a suitable scaffold for myoblast anchorage and that the custom-built bioreactor provided a qualified environment for the survival of the myoblasts on the polymeric scaffold. This PCL-based microfilament scaffold located inside the bioreactor proved to be a promising structure for the study of skeletal muscle models and can be used for mechanical stimulation studies in tissue engineering applications.
Artículo. Instituto Tecnológico de Costa Rica (ITCR). Escuela de Ciencia e Ingeniería de los Materiales, Escuela de Física, Escuela de Biología, 2022
Keywords: Andamios de tejido; Estimulación -- Biomecánica; Biorreactores; Ingeniería de tejidos; Células musculares; Viabilidad -- Células; Adhesión celular; In Vitro -- Tejidos; Tissue scaffolds; Stimulation -- Biomechanics; Bioreactors; Tissue engineering; Muscle cells; Viability -- Cells; Cell adhesion; In vitro -- Tissues; Research Subject Categories::MEDICINE::Morphology, cell biology, pathology::Cell biology; Research Subject Categories::TECHNOLOGY::Other technology::Medical engineering